How often do SmPCs Contain Contraindications and Special Warnings that are Specific for the Paediatric Population - Wimmer, Stefan; Rascher, Wolfgang; Neubert, Antje (Klinische Pädiatrie, 2019)
BACKGROUND: 3.2-3.8% of all medicine prescriptions for minor outpatients are off-label only because of the patients' age group. The younger, the more patients are affected by this issue. Only one fifth of the most commonly used medicines for newborns are licensed for this age group. The aim of this study is to analyse all German SmPCs whether they contain contraindications and warnings that specifically concern paediatric patients. METHODS: All available SmPCs were processed to search the sections Contraindications and Special warnings and precautions for information on paediatric age groups. Results were evaluated for differences between age groups, ATC classification and routes of application. RESULTS: 13547 SmPCs (22863 medicinal products) were evaluated. For 3603 (15.8%) medicinal products the SmPC contained contraindications for at least one paediatric age group. For 9687 (42.4%) medicinal products contraindications or warnings were found, including 2833 (12.4%) where all patients below 18 years were affected. Preterms were particularly affected (n=9581, 41.9%) as well as the ATC therapeutic subgroups contrast media (89.0%), cough and cold preparations (86.2%) and Corticosteroids (topical 88.2%, systemic 86.6%). Concerning liquids for oral use the proportion was higher than average (58.2%). CONCLUSION: It can be assumed that for most medicinal products the contraindications for paediatrics result from a lack of data and age specific formulations rather than from pharmacokinetic or -dynamic differences in paediatric patients. The EU Paediatric Regulation did not significantly stimulate the conduction of paediatric studies in off-patent medicines to this day.
EVALuna2:206642

Problems of drug therapy in pediatrics - Wimmer, Stefan; Rascher, Wolfgang (Kinderkrankenschwester, 2016)
EVALuna2:33998

The Safety of Drug Therapy in Children - Wimmer, Stefan; Neubert, Antje; Rascher, Wolfgang (Deutsches Ärzteblatt international, 2015)
1.7% of children taking medication on an outpatient basis in Germany have at least one adverse drug reaction (ADR). The corresponding figure for hospitalized children is estimated at 10% .This review is based on pertinent literature retrieved by a selective search in PubMed.According to reports submitted to the Drug Commission of the German Medical Association (Arzneimittelkommission der deutschen Ärzteschaft, AkdÄ), serious ADRs can arise, for example, after the administration of dimenhydrinate, ?-adrenergic nose drops, enemas containing phosphate, ACE inhibitors, angiotensin-2-receptor antagonists (sartans), and methylphenidate. The causes of ADRs include overdoses, drug administration despite contraindications, and inadequate monitoring of long-term treatment. Errors can also be made in communication, labeling, and drug administration. The risk of ADRs is especially high in off-label use. Computerized physician order entry systems, individual packaging and labeling of single doses, and the use of bar codes for patient and drug identification can help prevent such errors.The process of drug administration should be optimized through suitable interventions and electronic support, with due consideration of local circumstances. Clinical trials on children should be encouraged as a means of improving drug safety, and additional financial incentives should be created for trials concerning drugs that are off-patent. Physicians and pharmacists should take care to report adverse reactions as they are required to do by professional code, particularly in the case of new drugs, off-label use, or medication errors. A recognized national standard for dosing that can be implemented in computerized physician order entry systems is needed so that evidence-based pediatric dosages can be calculated.
EVALuna2:18938

Towards a Computable Data Corpus of Temporal Correlations between Drug Administration and Lab Value Changes - Newe, Axel; Wimmer, Stefan; Neubert, Antje; Becker, Linda; Prokosch, Hans-Ulrich; Beckmann, Matthias; Fietkau, Rainer; Forster, Christian; Neurath, Markus; Schett, Georg; Ganslandt, Thomas (PLoS ONE, 2015)
Background The analysis of electronic health records for an automated detection of adverse drug reactions is an approach to solve the problems that arise from traditional methods like spontaneous reporting or manual chart review. Algorithms addressing this task should be modeled on the criteria for a standardized case causality assessment defined by the World Health Organization. One of these criteria is the temporal relationship between drug intake and the occurrence of a reaction or a laboratory test abnormality. Appropriate data that would allow for developing or validating related algorithms is not publicly available, though. Methods In order to provide such data, retrospective routine data of drug administrations and temporally corresponding laboratory observations from a university clinic were extracted, transformed and evaluated by experts in terms of a reasonable time relationship between drug administration and lab value alteration. Result The result is a data corpus of 400 episodes of normalized laboratory parameter values in temporal context with drug administrations. Each episode has been manually classified whether it contains data that might indicate a temporal correlation between the drug administration and the change of the lab value course, whether such a change is not observable or whether a decision between those two options is not possible due to the data. In addition, each episode has been assigned a concordance value which indicates how difficult it is to assess. This is the first open data corpus of a computable ground truth of temporal correlations between drug administration and lab value alterations. Discussion The main purpose of this data corpus is the provision of data for further research and the provision of a ground truth which allows for comparing the outcome of other assessments of this data with the outcome of assessments made by human experts. It can serve as a contribution towards systematic, computerized ADR detection in retrospective data. With this lab value curve data as a basis, algorithms for detecting temporal relationships can be developed, and with the classification made by human experts, these algorithms can immediately be validated. Due to the normalization of the lab value data, it allows for a generic approach rather than for specific or solitary drug/lab value combination

Wie häufig betreffen Gegenanzeigen und Warnhinweise in deutschen Fachinformationen pädiatrische Patienten? - Wimmer, Stefan; Rascher, Wolfgang; Neubert, Antje (Klinische Pädiatrie, 2019)
Background 3.2-3.8% of all medicine prescriptions for minor outpatients are off-label only because of the patients' age group. The younger, the more patients are affected by this issue. Only one fifth of the most commonly used medicines for newborns are licensed for this age group. The aim of this study is to analyse all German SmPCs whether they contain contraindications and warnings that specifically concern paediatric patients. Methods All available SmPCs were processed to search the sections Contraindications and Special warnings and precautions for information on paediatric age groups. Results were evaluated for differences between age groups, ATC classification and routes of application. Results 13547 SmPCs (22863 medicinal products) were evaluated. For 3603 (15.8%) medicinal products the SmPC contained contraindications for at least one paediatric age group. For 9687 (42.4%) medicinal products contraindications or warnings were found, including 2833 (12.4%) where all patients below 18 years were affected. Preterms were particularly affected (n=9581, 41.9%) as well as the ATC therapeutic subgroups contrast media (89.0%), cough and cold preparations (86.2%) and Corticosteroids (topical 88.2%, systemic 86.6%). Concerning liquids for oral use the proportion was higher than average (58.2%). Conclusion It can be assumed that for most medicinal products the contraindications for paediatrics result from a lack of data and age specific formulations rather than from pharmacokinetic or -dynamic differences in paediatric patients. The EU Paediatric Regulation did not significantly stimulate the conduction of paediatric studies in off-patent medicines to this day.
CRIS-Team Scopus Importer:2019-07-26
Keywords: Contraindications; Drug safety; Off-Label-Use; Paediatrics; SmPC